Influence of Village Funds on Capital Accumulation and Community Empowerment - Saiful Amin; Nanda Widaninggar (Economics Development Analysis Journal, 2019)
This study aims at determining the effectiveness of the distribution and use of the Village Funds and their impacts on the increase in capital accumulation in Bondowoso Regency. This research is a quantitative research with a confirmatory approach because the researchers confirm the relationship between the research variables and test the hypotheses previously formulated. The analytical tool used is Structural Equity Modeling with the help of Lisrel 8.8 software. Respondents in this research amount to 75 villages in Bondowoso Regency that are selected based on purposive sampling (to select the subdistricts) and simple random sampling (to select villages/respondents). The results of research state that the effectiveness of the use of village funds has a significant influence on capital accumulation and empowerment of rural communities in Bondowoso Regency. Whereas capital accumulation has no significant influence on the empowerment of rural communities in Bondowoso Regency.